Childhood Maltreatment Experiences, Attachment, Sexual Offending: Testing a Theory. Issue 11 (June 2021) - Grady, Melissa D.; Yoder, Jamie; Brown, Adam
The aim of this study was to empirically examine the theoretical model proposed by Grady, Levenson, and Bolder used to explain the relationships between experiencing trauma, attachment styles, and risk factors associated with sexual offending. The specific risk factors tested were emotional, behavioral, and cognitive regulation deficits. The research questions were as follows: (1) What specific childhood traumatic experiences (physical and sexual abuse and/or other domestic trauma events) are associated with anxious-ambivalent and anxious-avoidant attachments? (2) Are anxious-ambivalent and anxious-avoidant attachment styles differentially linked to dysregulation outcomes (emotional, behavioral and cognitive shift, and inhibitions)? (3) Do insecure attachment styles explain why childhood trauma is associated with dysregulation? and (4) Do these early life experiences contribute to sexual offending behavior? The sample included 200 male youth adjudicated for either a sexual or nonsexual crime and living in the community or a residential facility. The average age of the youth was 17.17 years ( SD = 1.81 years). Structural equation modeling was used to determine the direct and indirect relationships between abuse and traumatic experiences, anxious-avoidant and ambivalent-anxious attachment styles, and regulation deficits. Authors found a direct relationship between physical abuse and both of the attachment styles, separately. Both anxious-ambivalent and anxious-avoidant attachment styles related similarly to regulation deficits. Separately, anxious-ambivalent and anxious-avoidant attachment styles served as mediators between physical abuse and regulation deficits. Sexual abuse predicted the later commission of sexual crimes with no influence from attachment style. Finally, domestic trauma independently predicted regulation deficits in the model that included anxious-ambivalent attachment but had no effect on deficits in the model that included anxious-avoidant attachment. Implications for treatment include the need to consider using attachment-based interventions and prevention strategies, and a trauma-informed approach when working with justice involved youth. Suggestions for future research are also discussed.